2013
DOI: 10.2478/pjvs-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Quality of milk of cows in the first lactation vs. presence of anti-Ostertagia antibodies in their milk

Abstract: Invasions of gastrointestinal nematodes in dairy cows may affect animals productivity. The most frequently detected internal parasite of dairy cattle is Ostertagia ostertagi. The objective of this study was to determine O. ostertagi invasion extensiveness in selected herds of dairy cattle, with special consideration to cows being in the first lactation, and to analyze the milk yield and contents of basic constituents of milk originating from sero-positive cows. Five herds of dairy cattle (403), with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Studies carried out in various countries show that the average extensiveness of gastrointestinal nematode infection (endoparasites) ranges from 61.96% in Mexico [17], 56% in Canada [18] to as much as 90% in Belgium and The Netherlands [19]. Polish studies, limited to the Warmia and Mazury voivodeship, showed extensiveness of infection at the level of 20% [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in various countries show that the average extensiveness of gastrointestinal nematode infection (endoparasites) ranges from 61.96% in Mexico [17], 56% in Canada [18] to as much as 90% in Belgium and The Netherlands [19]. Polish studies, limited to the Warmia and Mazury voivodeship, showed extensiveness of infection at the level of 20% [20].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in milk production in herds with confirmed infestation of Hypoderma spp. was estimated at 681.8 kg/year in the Warmia and Mazury voivodeship [20]. In the case of ectoparasites, losses associated with skin damage as well as changes in meat due to migration of larvae cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these effects on milk production, cattle helminths could also reduce calving interval and number of breeding at conception and increase 71 the mortality rate in a dairy herd (Walsh et al, 1995;Stromberg et al, 1997;Sanchez et al, 2002a;Delafosse, 2013). Interestingly, although heifers represent a capital investment for dairy farmers and are among the most vulnerable to this type of infections and production losses, little has been done to explore impacts of helminth infections in first-lactation heifers, with very few, inconclusive studies available (Blanco-Penedo et al, 2012;Liedtke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%